The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1038/jcbfm.1990.113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Unilateral Lesion of the Nucleus Basalis of Meynert on Brain Glucose Utilization in Callosotomized Baboons: A PET Study

Abstract: Summary: Prior work has demonstrated that unilateral lesions of the nucleus basalis of Meynert (NbM) in ba boons induce a marked reduction in glucose utilization of the ipsilateral cerebral cortex, linearly proportional to the depression in cortical choline acetyltransferase (ChAT) activity achieved. Unexpectedly, there was also marked hypometabolism of the contralateral cerebral cortex, and glucose utilization recovered gradually on both sides de spite persistent deficit in cortical ChAT activity. To in vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
(21 reference statements)
0
13
1
Order By: Relevance
“…Typically, glucose use was depressed 3-4 days postexcitotoxin-lesion, but recovered to basal levels within 4 weeks after unilateral lesions, and 4 months following bilateral lesions despite sustained ChAT deficits (9,37,44,47,60,61,80). This functional recovery most likely reflects the lack of cholinergic selectivity of these lesion paradigms, leading to incomplete cholinergic denervation.…”
Section: Reductions Of Cerebral Glucose Metabolism After Cholinergic mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, glucose use was depressed 3-4 days postexcitotoxin-lesion, but recovered to basal levels within 4 weeks after unilateral lesions, and 4 months following bilateral lesions despite sustained ChAT deficits (9,37,44,47,60,61,80). This functional recovery most likely reflects the lack of cholinergic selectivity of these lesion paradigms, leading to incomplete cholinergic denervation.…”
Section: Reductions Of Cerebral Glucose Metabolism After Cholinergic mentioning
confidence: 99%
“…Hence glucose use changes seen 18 weeks postcholinergic neuronal loss reflect alterations in well organized, functional pathways associated with the basal forebrain cholinergic system. Several previous studies in both rats and baboons used different lesion paradigms to assess glucose utilization after disrupting BF cholinergic projections (9,37,44,47,60,61,80). However, these investigations were compromised by the lack of a discrete, selective cholinotoxin.…”
Section: Reductions Of Cerebral Glucose Metabolism After Cholinergic mentioning
confidence: 99%
“…We limit this discussion to transhemispheric diaschisis, the terms "transhemispheric" or "interhemispheric" 11 being preferable to "transcallosal" because the contralateral effects of a unilateral insult may be mediated by neural pathways other than, or in addition to, the corpus callosum. 12 3 noted the importance of recovery of the deficits, or reversibility of the alterations, in diaschisis. Von Monakow wrote that "the effect of diaschisis, just as the effect of any type of shock, is in principle confined to a longer or shorter limited period (in its individual elements) and undergoes gradual regression in well-defined phases."…”
Section: Kempinskymentioning
confidence: 99%
“…A decrease in CMRglu bilaterally, ipsilateral greater than contralateral, was noted at day 4, with no significant resolution through day 39 and only a trend for recovery of the hemispheric asymmetry. 12 The authors, commenting on such a unilateral lesion, noted that the contralateral metabolic effects operate through extracallosal mechanisms and that an intact corpus callosum is important for recovery of CMRglu after insult, at least for recovery as rapidly as with an intact corpus callosum. However, Meyer et al 13 found in baboons 24-48 hours after corpus callosum section that bilateral CBF was not decreased by the corpus callosum section alone.…”
Section: Subacute Intermediate and Chronic Time Periodsmentioning
confidence: 99%
See 1 more Smart Citation